COMMUNICATIVE DICTATION FOR ADULT FOREIGN LANGUAGE LEARNERS IN UNIVERSITY ACADEMIC CONTEXTS: Received: 26th April 2023; Revised: 01st August 2023, 18th August 2023; Accepted: 21st August 2023 - Hull, Todd (PUPIL: International Journal of Teaching, Education and Learning, 2023)
Dictation is an effective tool in facilitating foreign language acquisition. But traditional dictation, while having some benefits for acquiring a foreign language, was neither engaging for students nor did it focus on the actual, real world communication that is fundamental to the communicative approach of today. Dictogloss introduced communicative dictation and has been used widely in classrooms around the world. But, however dictation is done in the classroom, it can 1) feel to adult learners at least somewhat like something for children and 2) even when designed for adults, typical dictation topics can be perceived to be more at home in a language institute than an academic university setting. This paper will summarize types of traditional dictation, outline the characteristics of dictogloss and how it is an improvement on traditional dictation, review some of the research on its additional benefits for acquiring a foreign language, and suggest how it can be used at the university level.